Analisis impor beras Indonesia - Sani, Yulia; Hodijah, Siti; Rosmeli, Rosmeli (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
This study aims to analyze the development of each variable and its effect on rice imports in Indonesia for the period 1998-2017. This research uses descriptive and quantitative analysis tools. The data used is time-series data or time series. To analyze this research, the